Posaconazole: A Review of Drug Interactions with HIV Antiretroviral Agents - Mara Poulakos; Amy Henneman; Simon Leung (MDPI AG, 2014)
The purpose of this review is to examine the literature for reports of clinically significant interactions noted amongst HIV antiretroviral medications when coadministered with posaconazole. A literature search was conducted to identify studies addressing drug interactions between posaconazole and HIV antiretroviral medications. Two pharmacokinetic studies and three clinical trials involving the administration of posaconazole to HIV-infected patients were identified. The pharmacokinetic studies involved concomitant administration of either a protease inhibitor (PI) or non-nucleoside reverse transcriptase inhibitor (NNRTI). Both studies showed alterations in systemic concentrations of either posaconazole or the HIV antiretroviral when administered together. Of the three clinical trials, all patients were on HIV antiretrovirals. However, their potential interaction with posaconazole was not explored. To date, there is no published literature regarding the interaction between maraviroc or elvitegravir and posaconazole. Dose adjustments for each are recommended when coadministered with strong CYP 3A4 inhibitors or inducers. Currently available literature points to the potential for clinically significant drug interactions when posaconazole is coadministered with HIV antiretrovirals, specifically NNRTIs and PIs. More studies are needed involving a wider range of HIV antiretrovirals to determine the significance of the interaction. Clinicians should be aware of this potentially significant interaction and avoid concomitant administration when possible. When available, consideration should be given to therapeutic drug monitoring of antiretroviral serum concentrations in select patients.